Polysubstance Use Among Veterans in Intensive PTSD Programs: Association With Symptoms and Outcomes Following Treatment. Issue 1 (2nd January 2019) - Bhalla, Ish P.; Stefanovics, Elina A.; Rosenheck, Robert A.
Abstract: Objective: A distinct group of patients has recently been described who experience polysubstance use disorder characterized by use of multiple addictive substances. This study examines baseline characteristics and longitudinal outcomes of a group of such patients in specialized intensive Veterans Health Administration posttraumatic stress disorder (PTSD) programs and followed 4 months after discharge.Methods: Patients with diagnosed PTSD or subsyndromal PTSD and who used a single substance at baseline were compared to those who used two or three and more than three different addictive substances on measures of PTSD symptom severity and functioning. Comparisons were also adjusted for differences in total days of any substance use and other potentially confounding factors. Patients were reclassified according to the number of substances used at follow-up and again compared on symptoms and functioning.Results: Bivariate analysis of baseline data ( N  = 8, 240) showed frequent polysubstance use ( n  = 3, 695, 44.8% of the sample) and that use of greater numbers of substances was associated with more severe PTSD symptoms as well as more total days of substance use. At follow-up after treatment, 58.2% of the original sample ( n  = 4, 797) was assessed. Polysubstance use was less frequent ( n  = 756, 15.8% of the follow-up sample), but showed a similar association with more severe symptoms, although differences were attenuated after adjusting for total days of substance use.Conclusions: Polysubstance use, conceptualized within the multimorbidity perspective, is associated with increased severity of PTSD symptoms among veterans with dual diagnoses requiring complex interventions, the evaluation of which will require innovative trial designs.